A new method to visualize obesity prevalence in Seattle‐King County at the census block level. (28th December 2017) - Drewnowski, A.; Buszkiewicz, J.; Aggarwal, A.; Cook, A.; Moudon, A. V.
Summary: Objective: The aim of this study is to map obesity prevalence in Seattle King County at the census block level. Methods: Data for 1, 632 adult men and women came from the Seattle Obesity Study I. Demographic, socioeconomic and anthropometric data were collected via telephone survey. Home addresses were geocoded, and tax parcel residential property values were obtained from the King County tax assessor. Multiple logistic regression tested associations between house prices and obesity rates. House prices aggregated to census blocks and split into deciles were used to generate obesity heat maps. Results: Deciles of property values for Seattle Obesity Study participants corresponded to county‐wide deciles. Low residential property values were associated with high obesity rates (odds ratio, OR: 0.36; 95% confidence interval, CI [0.25, 0.51] in tertile 3 vs. tertile 1), adjusting for age, gender, race, home ownership, education, and incomes. Heat maps of obesity by census block captured differences by geographic area. Conclusion: Residential property values, an objective measure of individual and area socioeconomic status, are a useful tool for visualizing socioeconomic disparities in diet quality and health.